Entrepreneurship: The Brain behind Successful Start-Ups. - Kwadade-Cudjoe, Francis (Archives of Business Research, 2019)
Entrepreneurs have been the most fascinating people on this planet, as most of the successful businesses are owned and championed by them. These are people who are leading the crusade on globalization where every person could be reached easily, using business as a tool. Most multi-national companies (MNCs) owned by entrepreneurs have opened branches in countries where natural resources as inputs for making targeted products/services are available. With the help of technology, entrepreneurs are succeeding in globalizing the world, and the emerging markets are equally being reached. However, there are many risks associated with starting a new business, popularly known as start-up, in addition to the problems of getting the initial capital and the uncertainty about the sustainability of the start-up. Entrepreneurs, therefore, go through numerous problems in order to see their dreams achieved.